COLLABORATIVE PROGRAM STRATEGY IN ENGLISH SPOKEN CLASS - Yuli Herman (Universitas Mahaputra Muhammad Yamin, 2019)
This research is derived from phenomena of finding the teaching technique that can accomodate the students’ feeling of comfortable in learning English. The collaborative program was used to answer this problem. The purpose of the research was to know whether or not the collaborative program could improve the EFL students’ speaking ability significantly. The research was conducted by using quasi experimental design which applies treatment class and control class as the source of data collection. The participants of the research were 16 students in each classes. They were the students who learnt Speaking 1 at Mahaputra M. Yamin University. Data was collected from oral test and classroom direct observation. The result of the test showed that there was a significant improvement toward students’ speaking ability through this technique where t- calculated score was 3.55 while the t-table score was 2.11. The observation data showed that all students had participated actively in the class discussion and created their own program in a fun way. This research has shown how the collaborative program can improve not only the skill of EFL students in speaking but also the way the students learn a topic with more fun and comprehensible